Hubungan antara ketokohan Gus Ali, identifikasi partai dan politik uang dengan pilihan masyarakat dalam Pilkada Kabupaten Sidoarjo tahun 2020: Studi kasus pilihan kepada pasangan Ahmad Muhdlor Ali-Subandi - Pramudhita, Prasasti Ayudya; Asfar, Muhammad (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
The regional head election (Pilkada) encompasses various intriguing phenomena, with political actions and voting decisions influenced by multiple factors. This study examined the impact of three key factors”Gus Ali's figure, Party Identification (Party ID), and Money Politics”on voters' decisions in the 2020 Sidoarjo Regional Head Election (Pilkada), specifically focusing on the Ahmad Muhdlor Ali-Subandi candidate pair. Utilizing quantitative methods with an explanatory approach grounded in voting behavior theory, the research found that Gus Ali's figure did not significantly influence voting decisions. In contrast, party identification and money politics showed a significant moderate correlation with voters' choices. Additionally, the study revealed that voters who identified with Gus Ali, had an emotional bond with Partai Kebangkitan Bangsa (PKB)-Partai Nasdem, and received monetary incentives were more likely to support the Ahmad Muhdlor Ali-Subandi pair.